Microinvasive surgery in the treatment of retinal detachment associated with an optic disk pit: 2 cases report - S. V. Sdobnokova; N. A. Troitskaya; N. Yu. Malakyan (Oftalʹmologiâ)
We report two cases of an 18-year-old boy with a left optic disc pit and associated retinal edema of the macula and 47-year-old woman with an optic disk pit and associated retinal detachment of the macula. First was treated by intravitreal injection of Lucentis. Woman was treated by gas tamponade as a primary procedure. Both procedures resulted in complete resolution of subretinal fluid andincrease of visual acuity. We conclude that microinvasive surgery can be effective treatment of this disease.